Perencanaan Merdeka Belajar Berbasis Literasi Dalam Pembelajaran Ipa Di SMP Negeri 33 Jakarta Selatan - Medi Yansyah; Dawam Ashidiqie; Fadli Firdaus; Dwi Rudy Prasetyo; Antonius Rino Vanchapo; Fitrisiswanty Fitrisiswanty (Departement of Mathematics Education, 2023)
Literacy-based ndependent learning planning s mportant to be applied n the science learning process. The principal as the manager of SMP negeri 33 Jakarta selatanwas very enthusiastic n welcoming the concept of ndependent learning. Teachers and observers of education at smp negeri 33 Jakarta selatanhope that the concept of ndependent learning that will be applied by the school will bring positive changes to the development of the quality of education at that school because this will help provide students with the skills needed n the 21st century. The results showed that, planning n the literacy-based ndependent learning program n science learning at smp negeri 33 Jakarta selatanwas conducted by holding deliberations with various related elements. Planning lessons was carried out n the classroom, and outside, planning n learning was cnducted by carrying out a literacy movement that has 2 goals, namely general goals and specific goals. Planning constraints n the literacy-based ndependent learning program n science learning at smp negeri 33 Jakarta selatan consists of 3 obstacles, namely: 1). Lack of human resources who can understand literacy programs properly and correctly; 2) time for literacy activities at school; and 3) the school library s only limited to the school library, and the library collection only provides school books, very few other additional books.